Effect Of Hexagonal Boron Nitride Nanoparticles As An Additive On The Extreme Pressure Properties Of Engine Oil - Muhammad Ilman Hakimi Chua, Abdullah; Mohd Fadzli, Abdollah; Noreffendy, Tamaldin; Hilmi, Amiruddin; Nur Rashid, Mat Nuri (Emerald Group Publishing Limited, 2016)
Purpose – This paper aims to investigate the effect of hexagonal boron nitride (hBN) nanoparticles on extreme pressure (EP) properties when used as an additive in lubricating oil. Design/methodology/approach – The nano-oil was prepared by dispersing an optimal composition of 0.5 vol. per cent of 70 nm hBN in SAE 15W-40 diesel engine oil using a sonication technique. The tribological testing was performed using a four-ball tribometer according to the ASTM standard. Findings – It was found that the nano-oil has a potential to decelerate the seizure point on the contact surfaces, where higher EP can be obtained. More adhesive wear was observed on the worn surfaces of ball bearing lubricated with SAE 15W-40 diesel engine oil as compared with the nano-oil lubrication. Originality/value – The results of the experimental studies demonstrated the potential of hBN as an additive for improving the load-carrying ability of lubricating oil.